Primary Care of Men Who Have Sex With Men in the U.S. Military in the Post-Don't Ask, Don't Tell Era: A Review of Recent Progress, Health Needs, and Challenges. Issue 3 (1st March 2017) - Campbell, Wesley R.; Jahan, Mojgan; Bavaro, Mary F.; Carpenter, Robert J.
ABSTRACT: Background: With repeal of "Don't Ask, Don't Tell" (DADT) in 2011 and the Supreme Court decision regarding Section 3 of the Defense of Marriage Act (DOMA) in 2013, military providers are now able to openly address unique health needs of lesbian, gay, and bisexual (LGB) service members and their same-sex spouse beneficiaries. These federal laws created health care barriers, either real or perceived, between providers and patients and often limited medical research involving LGB patients in the Military Health System (MHS). Men who have sex with men (MSM), the largest proportion of LGB service members, represent a segment of the population with the highest risks for disparities in primary care with regard to sexual health and mental health disorders. We provide a review of available research about this military population, in addition to a review of specific health care needs of the MSM patient in order to aid the primary care provider with screening, testing, and counseling. Methods: A structured literature search was conducted to identify recent literature pertaining to health needs of U.S. military MSM service members. In addition, a review of applicable clinical guidelines, Department of Defense policies, and expert opinion was used to identify areas of particular relevance. Findings: There is little published to characterize the MSM population and their health needs as beneficiaries of the MHS. Only recently have directed assessments of the active-duty MSM patient population been pursued in the post-DADT, DOMA era. Unique needs of the MSM patient identified center around both sexual and mental health, disparities that are paralleled within the nonmilitary MSM population. Population-specific epidemiology driving risk for sexually transmitted illnesses, substance abuse, and mental health disorders are identified and used to inform preventive medicine recommendations for the MSM patient. In addition, resources on MSM health for the health provider are included. Discussion/Impact/Recommendation: The MHS at large now openly serves the MSM population and is making progress toward addressing their unique health needs. Despite ongoing challenges to address remaining disparities, MSM patients, beneficiaries, and primary providers are now more able to have frank, open discussions about specific health needs of this minority segment of the U.S. military without fear of reprisal.